Efficiency of National Zakat Institutions on Increasing Muzakki from 2015-2016 - Sunan Fanani, Ahmad Maulana, (Opción, 2020)
Zakat is an obligation for Muslims who meet certain conditions (muzakki). Indonesia, the largest Muslim country, has facilitated citizens to channel zakat to who are entitled. The purpose of this study was to analyze the efficiency of a zakat institution on the growth of the muzakki numbers in Indonesia. Results showed that there is efficiency in LAZ Mandiri with a score of 0.76 in 2016 & needs to refer to LAZ Nahdlatul Ulama to improve its performance. Moreover, organizational performance of zakat management institutions has not been optimally increasing the number of muzakki in Indonesia.